GollumFit: An icecube open-source framework for binned-likelihood neutrino telescope analyses - R. Abbasi; M. Ackermann; J. Adams; S.K. Agarwalla; J.A. Aguilar; M. Ahlers; J.M. Alameddine; N.M. Amin; K. Andeen; C. Argüelles; Y. Ashida; S. Athanasiadou; et al. (Computer Physics Communications, 2026)

Association between cardiovascular-kidney-metabolic syndrome and risks of 14 age-related health outcomes in primary prevention older population - Zhen Zhou; Kevan R. Polkinghorne; Andrew M. Tonkin; Robyn L. Woods; Anping Cai; Sophia Zoungas; Michelle A. Fravel; Michael E. Ernst; Chao Zhu; Mark Nelson; Johannes T. Neumann; Kerry M. Sheets; et al. (GeroScience, 2026)

Elevated alpha-1 antitrypsin and C-reactive protein: association on all-cause and cause-specific mortality in older adults - Cammie Tran; Hans G. Schneider; Que T. Lam; Johannes T. Neumann; Flavia Cicuttini; Chenglong Yu; Zhen Zhou; Mark R. Nelson; Andrew M. Tonkin; Daniel Clayton-Chubb; Sultana Monira Hussain; Peter D. Fransquet; et al. (GeroScience, 2025)

Avenues towards reconciling wild and managed bee proponents - Alexis L. Beaurepaire; Katja Hogendoorn; David Kleijn; Gard W. Otis; Simon G. Potts; Theresa L. Singer; Samuel Boff; Christian Pirk; Josef Settele; Robert J. Paxton; Nigel E. Raine; Simone Tosi; et al. (Trends in Ecology & Evolution, 2025)

There is a trade-off between forest productivity and animal biodiversity in Europe - C. N. Khamila; T. A. Groen; A. G. Toxopeus; L. Santini; M. Neumann; C. Van Swaay; H. Sierdsema (Biodiversity and Conservation, 2023)
While forest productivity and biodiversity are expected to be correlated, prioritizing either forest productivity or biodiversity can result in different management. Spatial quantification of the congruence between areas suitable for either one can inform planning. Here we quantify the relationship between net primary productivity of European forests and biodiversity of mammals, birds, reptiles, amphibians, and butterflies both separately and in combination, and map their spatial congruence. We used richness maps obtained by stacking species distribution models for these animal species, and average net primary production from 2000 to 2012 using moderate resolution imaging spectroradiometer (MODIS) data. We tested how biodiversity and primary productivity are correlated and quantified the spatial congruence of these two sources. We show the areas where high or low productivity co-occur with high or low biodiversity using a quantile-based overlay analysis. Productivity was positively correlated to overall biodiversity and mammal, herptile and butterfly biodiversity, but biodiversity of birds showed a weak negative correlation. There were no significant differences in the strength of relationship across species groups, while herptiles had stronger relationships with productivity compared to other groups. Overlap analysis revealed significant spatial overlap between productivity and biodiversity in all species groups, except for birds. High value areas for both productivity and biodiversity in all species groups, except birds, co-occurred in the Mediterranean and temperate regions. The areas with high biodiversity of birds are mainly found in the boreal areas of Europe, while for all other species groups these areas are mostly located on the Iberian Peninsula and the Balkan ranges. Based on the presented maps, areas where regulating wood production activities to conserve species can be identified. But the maps also help to identify areas where either biodiversity or productivity is high and focusing on just one aspect is more straightforward.

Monitoring and evaluation of maritime spatial planning – A review of accumulated practices and guidance for future action - S.W.K. van den Burg; M. Skirtun; O. van der Valk; W. Rossi Cervi; T. Selnes; T. Neumann; J. Steinmann; G. Arora; P. Roebeling (Marine Policy, 2023)

Zooplankton exposure to microplastic contamination in a estuarine plume-influenced region, in Northeast Brazil - C.D.M. Lima; M. Melo Júnior; S.H.L. Schwamborn; F. Kessler; L.A. Oliveira; B.P. Ferreira; G. Mugrabe; J. Frias; S. Neumann-Leitão (Environmental Pollution, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Geochemistry of deep Tunguska Basin sills, Siberian Traps: correlations and potential implications for the end-Permian environmental crisis - S. Callegaro; H. H. Svensen; E. R. Neumann; A. G. Polozov; D. A. Jerram; F. M. Deegan; S. Planke; O. V. Shiganova; N. A. Ivanova; N. V. Melnikov (Contributions to Mineralogy and Petrology, 2021)
A vast portion of the plumbing system of the Siberian Traps Large Igneous Province (STLIP) is emplaced in the Tunguska Basin, where borehole data reveal ubiquitous and abundant sills with great lateral extension. These intrusions intersect Cambrian–Ordovician evaporite, carbonate and siliciclastic series, and locally coal-bearing Permian host rocks, with a high potential for thermogenic gas generation. Here we present new geochemical data from 71 magmatic and 4 sedimentary rock samples from the Tunguska Basin center and periphery, recovered from 15 deep sills intercepted by boreholes. The studied samples are all low-Ti basalt and basaltic andesites, confirming absence of high-Ti and alkaline STLIP magmatism in the Tunguska Basin. The sills derive from picritic parental melts produced by extensive melting of a mantle source with recycled crustal components below a thinned lithosphere (50–60 km), within the spinel stability field. The mantle source was dominantly peridotitic, with enriched pyroxenitic domains formed by recycled lower crust, in agreement with previous models for the main tholeiitic STLIP phase. Limited amounts (up to 5%) of highly radiogenic granitoids or moderately radiogenic metapelites were assimilated in upper crustal magma reservoirs. After emplacement, sills intruded in Cambrian evaporites assimilated marlstones and interacted with the evaporitic host rocks, probably via fluids and brines. This is the first time that such process is described in subvolcanic rocks from all across the volcanic basin. The sills are correlated geochemically with the established chemostratigraphy for the on-craton STLIP lava piles and intrusions (Norilsk region). Sills correlated with the Morongovsky–Mokulaevsky Fm. and the Norilsk-type intrusions are the most voluminous, present all across the central Tunguska Basin, and bear the strongest evidence of interaction with evaporites. Massive discharge of thermogenic volatiles is suggested by explosive pipes and hydrothermal vent structures throughout the Tunguska Basin. We propose that this voluminous pulse of magmatism is a good candidate for the hitherto unidentified early intrusive phase of the STLIP, and may link the deep Tunguska basin sills to the end-Permian environmental crisis.

Correction to: Strength of correlation between wildlife collision data and hunting bags varies among ungulate species and with management scale - Wiebke Neumann; Fredrik Widemo; Navinder J. Singh; Andreas Seiler; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2020)

Strength of correlation between wildlife collision data and hunting bags varies among ungulate species and with management scale - Wiebke Neumann; Fredrik Widemo; Navinder J. Singh; Andreas Seiler; Joris P. G. M. Cromsigt (European Journal of Wildlife Research, 2020)
Most European ungulate species are increasing in numbers and expanding their range. For the management and monitoring of these species, 64% of European countries rely on indirect proxies of abundance (e.g., hunting bag statistics). With increasing ungulate numbers, data on ungulate-vehicle collisions (UVC) may provide an important and inexpensive, complementary data source. Currently, it is unclear how bag statistics compare with UVC. A direct comparison of these two indices is important because both are used in ungulate management. We evaluated the relationship between UVC and ungulate hunting bags across bioclimatic, regional, and local scales, using five time lags (t −3 to t +1 ) for the five most common wild ungulate species in Sweden. For all species, hunting bags and UVC correlated positively, but correlation strength and time lags varied across scales and among species. The two indices correlated most strongly at the local management scale. Correlation between both indices was strong for the smaller deer species and wild boar, in particular, but much weaker for moose where we found the best fit using a 2-year time lag. For the other species, indices from the same year correlated best. We argue that the reason for moose data behaving differently is that, in Sweden, moose are formally managed using a 3-year time plan, while the other species are not. Accordingly, moose hunting bags are influenced more strongly by density-independent processes than bags of the other species. Consequently, the mismatch between the two indices may generate conflicting conclusions for management depending on the method applied.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

Phylogeography of the striped field mouse, Apodemus agrarius (Rodentia: Muridae), throughout its distribution range in the Palaearctic region - Alice Latinne; Miguel Navascués; Marina Pavlenko; Irina Kartavtseva; Rainer G. Ulrich; Marie-Laure Tiouchichine; Gilles Catteau; Hela Sakka; Jean-Pierre Quéré; Galina Chelomina; Aleksey Bogdanov; Michal Stanko; et al. (Mammalian Biology, 2020)

Assessment of Uncertainties in Scenario Simulations of Biogeochemical Cycles in the Baltic Sea - H. E. Markus Meier; Moa Edman; Kari Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2019)

Limitations of Weight Velocity Analysis by Commercial Computer Program Growth Analyser Viewer Edition - Martin J. C. van Gemert; Cornelis M. A. Bruijninckx; Ton G. van Leeuwen; H. A. Martino Neumann; Pieter J. J. Sauer (Annals of Biomedical Engineering, 2019)

Correction to: Diel plant water use and competitive soil cation exchange interact to enhance NH4+ and K+ availability in the rhizosphere - Javier F. Espeleta; Zoe G. Cardon; K. Ulrich Mayer; Rebecca B. Neumann (Plant and Soil, 2018)

Assessment of Eutrophication Abatement Scenarios for the Baltic Sea by Multi-Model Ensemble Simulations - H. E. Markus Meier; Moa K. Edman; Kari J. Eilola; Manja Placke; Thomas Neumann; Helén C. Andersson; Sandra-Esther Brunnabend; Christian Dieterich; Claudia Frauen; René Friedland; Matthias Gröger; Bo G. Gustafsson; et al. (Frontiers in Marine Science, 2018)

Global biodiversity research tied up by juridical interpretations of access and benefit sharing - D. Neumann; A. V. Borisenko; J. A. Coddington; C. L. Häuser; C. R. Butler; A. Casino; J. C. Vogel; G. Haszprunar; P. Giere (Organisms Diversity & Evolution, 2018)

Formation of Si-Al-Mg-Ca-rich zoned magnetite in an end-Permian phreatomagmatic pipe in the Tunguska Basin, East Siberia - Else-Ragnhild Neumann; Henrik H. Svensen; Alexander G. Polozov; Øyvind Hammer (Mineralium Deposita, 2017)

Diel plant water use and competitive soil cation exchange interact to enhance NH4 + and K+ availability in the rhizosphere - Javier F. Espeleta; Zoe G. Cardon; K. Ulrich Mayer; Rebecca B. Neumann (Plant and Soil, 2017)

Developments in pre-treatment methods to improve anaerobic digestion of sewage sludge - P. Neumann; S. Pesante; M. Venegas; G. Vidal (Reviews in Environmental Science and Bio/Technology, 2016)

No need to breed for enhanced colonization by arbuscular mycorrhizal fungi to improve low-P adaptation of West African sorghums - Willmar L. Leiser; Marcus O. Olatoye; H. Frederick W. Rattunde; Günter Neumann; Eva Weltzien; Bettina I. G. Haussmann (Plant and Soil, 2016)

Jellyfish diversity and distribution patterns in the tropical S outhwestern A tlantic - Lúcia Maria O. Gusmão; Xiomara Franchesca G. Diaz; Mauro de Melo; Ralf Schwamborn; Sigrid Neumann‐Leitão (Marine Ecology, 2015)
Jellyfish are often the most prominent components of plankton, with severe consequences for fisheries and tourism. However, in tropical regions, there is much uncertainty about these consequences due to the lack of basic data. Our objective was to improve the knowledge about jellyfish in the W estern A tlantic, with an emphasis on understanding diversity, abundance, and distribution patterns. Samples were collected at 34 stations in 1995 using a 300‐μm‐mesh B ongo net. The 21 species identified belonged to Hydromedusae (11), Siphonophora (nine), and Scyphomedusae (one). The overall mean density was low (5.2 ± 5.3 ind. m −3 ). Total H ydromedusae biomass was 130.86 mg C m −3 , and total S iphonophora biomass was 19.04 mg C m −3 . Chelophyes appendiculata ( E schscholtz, 1829) was the most frequent species captured in the oceanic samples, and A glaura hemistoma ( P éron & L esueur, 1810) was the most common in the neritic region. The latter species is sometimes characterized as a bloom associated with the most polluted and eutrophic river plumes. The main role of jellyfish species in the area is as a higher‐order carnivore. A cross‐shelf significant difference (P

Improving cross-sectoral climate change adaptation for coastal settlements: insights from South East Queensland, Australia - S. Serrao-Neumann; F. Crick; B. Harman; M. Sano; O. Sahin; R. van Staden; G. Schuch; S. Baum; D. Low Choy (Regional Environmental Change, 2014)

Adapting to climate change through urban water management: a participatory case study in Indonesia - Dewi G. C. Kirono; Silva Larson; Grace Tjandraatmadja; Anne Leitch; Luis Neumann; Shiroma Maheepala; Roland Barkey; Amran Achmad; Mary Selintung (Regional Environmental Change, 2014)

The production and turnover of extramatrical mycelium of ectomycorrhizal fungi in forest soils: role in carbon cycling - A. Ekblad; H. Wallander; D. L. Godbold; C. Cruz; D. Johnson; P. Baldrian; R. G. Björk; D. Epron; B. Kieliszewska-Rokicka; R. Kjøller; H. Kraigher; E. Matzner; et al. (Plant and Soil, 2013)

Depositional systems in the Mt Isa Inlier from 1800 Ma to 1640 Ma: Implications for Zn–Pb–Ag mineralisation - P. N. Southgate; N. L. NEUMANN; G. M. GIBSON (Australian Journal of Earth Sciences, 2013)

Performance of a novel microarray multiplex PCR for the detection of 23 respiratory pathogens (SYMP-ARI study) - S. Bierbaum; N. Königsfeld; N. Besazza; K. Blessing; G. Rücker; U. Kontny; R. Berner; M. Schumacher; J. Forster; V. Falcone; C. Sand; A. Essig; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Impact of Climate Change on Ecological Quality Indicators and Biogeochemical Fluxes in the Baltic Sea: A Multi-Model Ensemble Study - H. E. Markus Meier; Bärbel Müller-Karulis; Helén C. Andersson; Christian Dieterich; Kari Eilola; Bo G. Gustafsson; Anders Höglund; Robinson Hordoir; Ivan Kuznetsov; Thomas Neumann; Zohreh Ranjbar; Oleg P. Savchuk; et al. (Ambio, 2012)

Reconstructing the Development of Baltic Sea Eutrophication 1850–2006 - Bo G. Gustafsson; Frederik Schenk; Thorsten Blenckner; Kari Eilola; H. E. Markus Meier; Bärbel Müller-Karulis; Thomas Neumann; Tuija Ruoho-Airola; Oleg P. Savchuk; Eduardo Zorita (Ambio, 2012)

Orbit determination of the Lunar Reconnaissance Orbiter - Erwan Mazarico; D. D. Rowlands; G. A. Neumann; D. E. Smith; M. H. Torrence; F. G. Lemoine; M. T. Zuber (Journal of Geodesy, 2012)

Plant-borne flavonoids released into the rhizosphere: impact on soil bio-activities related to plant nutrition. A review - S. Cesco; T. Mimmo; G. Tonon; N. Tomasi; R. Pinton; R. Terzano; G. Neumann; L. Weisskopf; G. Renella; L. Landi; P. Nannipieri (Biology and Fertility of Soils, 2012)

Novel Types of Frontotemporal Lobar Degeneration: Beyond Tau and TDP-43 - Ian R. A. Mackenzie; Manuela Neumann; Nigel J. Cairns; David G. Munoz; Adrian M. Isaacs (Journal of Molecular Neuroscience, 2011)

Combination therapy with dexamethasone and osteoprotegerin protects against arthritis-induced bone alterations in antigen-induced arthritis of the rat - P. Oelzner; S. Fleissner-Richter; R. Bräuer; G. Hein; G. Wolf; T. Neumann (Inflammation Research, 2010)

Strong genetic differentiation and postglacial origin of populations in the marine midge Clunio marinus (Chironomidae, Diptera) - TOBIAS S. KAISER; DIETRICH NEUMANN; DAVID G. HECKEL; THOMAS U. BERENDONK (Molecular Ecology, 2010)

Geodetic constraints from multi-beam laser altimeter crossovers - Erwan Mazarico; G. A. Neumann; D. D. Rowlands; D. E. Smith (Journal of Geodesy, 2010)

On the Photophysical Properties of New Luminol Derivatives and their Synthetic Phthalimide Precursors - Raúl Pérez-Ruiz; Robert Fichtler; Yrene Diaz Miara; Matthieu Nicoul; Dominik Schaniel; Helfried Neumann; Matthias Beller; Dirk Blunk; Axel G. Griesbeck; Axel Jacobi von Wangelin (Journal of Fluorescence, 2010)

Vorgaben für Rettung und Brandschutz für die Vortriebe des Koralmtunnels - G. Harer; S. Hubmann; E. Kaiser; D. Lauffer-Neumann (BHM Berg- und Hüttenmännische Monatshefte, 2010)

New SHRIMP age constraints on the timing and duration of magmatism and sedimentation in the Mary Kathleen Fold Belt, Mt Isa Inlier, Australia - N. L. Neumann; G. M. Gibson; P. N. Southgate (Australian Journal of Earth Sciences, 2009)

An integrated river basin-coast-sea modelling scenario for nitrogen management in coastal waters - G. Schernewski; H. Behrendt; T. Neumann (Journal of Coastal Conservation, 2008)

Composition and thermal structure of the lithosphere beneath the Ethiopian plateau: evidence from mantle xenoliths in basanites, Injibara, Lake Tana Province - S. Ferrando; M. L. Frezzotti; E.-R. Neumann; G. De Astis; A. Peccerillo; A. Dereje; Y. Gezahegn; A. Teklewold (Mineralogy and Petrology, 2008)

Osteoprotegerin reduces the loss of periarticular bone mass in primary and secondary spongiosa but does not influence inflammation in rat antigen-induced arthritis - T. Neumann; P. Oelzner; P. K. Petrow; K. Thoss; G. Hein; G. Stein; R. Bräuer (Inflammation Research, 2006)

Assessing the extent of induced leakage to an urban aquifer using environmental tracers: an example from Bishkek, capital of Kyrgyzstan, Central Asia - Brian L. Morris; W. George Darling; Daren C. Gooddy; Rafael G. Litvak; Ilka Neumann; Ekaterina J. Nemaltseva; Inna Poddubnaia (Hydrogeology Journal, 2006)

Rare royal families in honeybees, Apis melliferas - Robin F. A. Moritz; H. Michael; G. Lattorff; Peter Neumann; F. Bernhard Kraus; Sarah E. Radloff; H. Randall Hepburn (The Science of Nature, 2005)

Rare royal families in honeybees, Apis mellifera - Robin F. A. Moritz; H. Michael G. Lattorff; Peter Neumann; F. Bernhard Kraus; Sarah E. Radloff; H. Randall Hepburn (The Science of Nature, 2005)

Genetic spatial structure of European common hamsters ( Cricetus cricetus ) — a result of repeated range expansion and demographic bottlenecks - K. NEUMANN; J. R. MICHAUX; S. MAAK; H. A. H. JANSMAN; A. KAYSER; G. MUNDT; R. GATTERMANN (Molecular Ecology, 2005)
The spatial genetic structure of common hamsters ( Cricetus cricetus ) was investigated using three partial mitochondrial (mt) genes and 11 nuclear microsatellite loci. All marker systems revealed significant population differentiation across Europe. Hamsters in central and western Europe belong largely to two allopatric mitochondrial lineages south and northwest of the Carpathian and Sudetes. The southern group, ‘Pannonia’, comprises populations inside the Carpathian basin (Czech Republic, Hungary) while the second group, ‘North’, includes hamsters from Belgium, the Netherlands, France, and Germany. Isolation of the lineages is maintained by a combination of geographical and ecological barriers. Both main phylogeographical groups show signs of further subdivision. North is separated into highly polymorphic central German and less polymorphic western populations, which most likely split during late glacial expansion (15 000–10 000 bp ). Clock estimates based on haplotype distributions predict a divergence of the two major lineages 85 000–147 000 bp . Expansion times fall during the last glaciation (115 000–10 000 bp ) corroborating fossil data, which identify Cricetus cricetus as characteristic of colder climatic phases. Despite the allopatry of mt haplotypes, there is an overlap of nuclear microsatellite alleles between phylogeographical units. Although there are strong evidence that Pannonian hamsters have persisted inside the Carpathian basin over the last 50 000 years, genetic differentiation among European hamsters has mainly been caused by immigration from different eastern refugia. Possible source populations are likely to be found in the Ukrainian and the southern Russian plains — core areas of hamster distribution. From there, hamsters have repeatedly expanded during the Quaternary.

The influence of redox conditions in soils on extraplasmatic Fe-loading of plant roots - S. Fiedler; O. Strasser; G. Neumann; V. Römheld (Plant and Soil, 2004)

Biomonitoring of aromatic amines VI: determination of hemoglobin adducts after feeding aniline hydrochloride in the diet of rats for 4 weeks - I. Zwirner-Baier; K. Deckart; R. Jckh; H.-G. Neumann (Archives of Toxicology, 2003)

A technical note for using microsatellite DNA analyses in haploid male DNA pools of social Hymenoptera - R. F. A. Moritz; H. Scharpenberg; H. M. G. Lattorff; P. Neumann (Insectes Sociaux, 2003)

Somatic embryogenesis and DNA organization of genomes from selected Daucus species - J. Imani; L. Tran Thi; G. Langen; B. Arnholdt-Schmitt; S. Roy; C. Lein; A. Kumar; K.-H. Neumann (Plant Cell Reports, 2001)

Cereal/legume rotations affect chemical properties and biological activities in two West African soils - S. Alvey; M. Bagayoko; G. Neumann; A. Buerkert (Plant and Soil, 2001)

Hemoglobin adducts of epoxybutene in workers occupationally exposed to 1,3-butadiene - P. Begemann; R.J. Srám; H.-G. Neumann (Archives of Toxicology, 2001)

Root-induced increases in soil pH and nutrient availability to field-grown cereals and legumes on acid sandy soils of Sudano-Sahelian West Africa - M. Bagayoko; S. Alvey; G. Neumann; A. Buerkert (Plant and Soil, 2000)

Recommendations for the categorization of germ cell mutagens - I.-D. Adler; U. Andrae; P. Kreis; H.-G. Neumann; R. Thier; D. Wild (International Archives of Occupational and Environmental Health, 2000)

Characterization of a novel 21-kb deletion, CFTRdele2,3(21 kb), in the CFTR gene: a cystic fibrosis mutation of Slavic origin common in Central and East Europe - T. Dörk; M. Macek Jr; F. Mekus; B. Tümmler; J. Tzountzouris; T. Casals; A. Krebsová; M. Koudová; I. Sakmaryová; M. Macek Sr; V. Vávrová; D. Zemková; et al. (Human Genetics, 2000)

Characterization of the cys gene locus from Allochromatium vinosum indicates an unusual sulfate assimilation pathway* - Sebastian Neumann; Astrid Wynen; Hans G. Trüper; Christiane Dahl (Molecular Biology Reports, 2000)

The influence of cytochrome P450 1A1 and glutathione S-transferase M1 genotypes on biomarker levels in coke-oven workers - G. Brescia; L. Celotti; E. Clonfero; H. G. Neumann; A. Forni; V. Foà; M. Pisoni; G. M. Ferri; G. Assennato (Archives of Toxicology, 1999)

Sulfate reduction in surface sediments of the southeast Atlantic continental margin between 15°38'S and 27°57'S (Angola and Namibia) - Timothy G. Ferdelman; Henrik Fossing; Kirsten Neumann; Horst D. Schulz (Limnology and Oceanography, 1999)
Sulfate reduction rates in the surface sediments from 17 stations from an along‐slope transect (1,300 m) and from a cross‐slope transect (855–4,766 m) were determined in the continental margin sediments of the Benguela Upwelling system. Profiles at all sites in the upwelling area showed increasing sulfate reduction rates from near zero at the surface to a peak at 2–5 cm (up to 29 nmol cm −3 d −1 ) and then decreasing exponentially with depth to near background rates at 10–20 cm depth ( −3 d −1 ). Depth‐integrated sulfate reduction rates were greatest at 1,300 m and decreased exponentially with water depth. Along the transect following the 1,300‐m isobath, depth‐integrated sulfate reduction rates were highest in the north Cape Basin (1.16 +/− 0.23 mmol m −2 d −1 ), decreased over the Walvis Ridge (0.67 +/− 0.02 mmol m −2 d −1 ), and were lowest in the south Angola Basin (0.31 +/− 0.23 mmol m −2 d −1 ). Depth‐integrated sulfate reduction rates were consistent with the known pattern of coastal upwelling intensities and were also strongly correlated with surface organic carbon concentrations. Sulfate reduction rates, both as a function of depth and in comparison with sediment trap data, indicated that lateral downslope transport of organic carbon occurs. Sulfate reduction was estimated to account for 20–90% of the published rates of total oxygen consumption for the sediments at 1,300 m depth and 3–16% of sediments from 2,000 to 3,000 m depth. Comparison of the sulfate reduction rate profiles with the published diffusive oxygen uptake rates showed that the kinetics of oxygen utilization in the surface sediments are much faster than those for anaerobic organic carbon remineralization, although the underlying cause of the difference was not clear.

Root excretion of carboxylic acids and protons in phosphorus-deficient plants - G. Neumann; V. Römheld (Plant and Soil, 1999)

Interface between haustoria of parasitic members of the Scrophulariaceae and their hosts: A histochemical and immunocytochemical approach - U. Neumann; B. Vian; H. C. Weber; G. Sall (Protoplasma, 1999)

Effects of climatic variability on the annual carbon sequestration by a boreal aspen forest - W. J. Chen; T. A. Black; P. C. Yang; A. G. Barr; H. H. Neumann; Z. Nesic; P. D. Blanken; M. D. Novak; J. Eley; R. J. Ketler; R. Cuenca (Global Change Biology, 1999)
To evaluate the carbon budget of a boreal deciduous forest, we measured CO 2 fluxes using the eddy covariance technique above an old aspen (OA) forest in Prince Albert National Park, Saskatchewan, Canada, in 1994 and 1996 as part of the Boreal Ecosystem‐Atmosphere Study (BOREAS). We found that the OA forest is a strong carbon sink sequestering 200 ± 30 and 130 ± 30 g C m –2 y –1 in 1994 and 1996, respectively. These measurements were 16–45% lower than an inventory result that the mean carbon increment was about 240 g C m –2 y –1 between 1919 and 1994, mainly due to the advanced age of the stand at the time of eddy covariance measurements. Assuming these rates to be representative of Canadian boreal deciduous forests (area ≈ 3 × 10 5 km 2 ), it is likely they can sequester 40–60 Tg C y –1 , which is 2–3% of the missing global carbon sink. The difference in carbon sequestration by the OA forest between 1994 and 1996 was mainly caused by the difference in leaf emergence date. The monthly mean air temperature during March–May 1994, was 4.8 °C higher than in 1996, resulting in leaf emergence being 18–24 days earlier in 1994 than 1996. The warm spring and early leaf emergence in 1994 enabled the aspen forest to exploit the long days and high solar irradiance of mid‐to‐late spring. In contrast, the 1996 OA growing season included only 32 days before the summer solstice. The earlier leaf emergence in 1994 resulted 16% more absorbed photosynthetically active radiation and a 90 g C m –2 y –1 increase in photosynthesis than 1996. The concomitant increase in respiration in the warmer year (1994) was only 20 g C m –2 y –1 . These results show that an important control on carbon sequestration by boreal deciduous forests is spring temperature, via the influence of air temperature on the timing of leaf emergence.

Changes in the classification of carcinogenic chemicals in the work area - Hans-Gnter Neumann; Spyridon Vamvakas; Heinz Walter Thielmann; Hans-Peter Gelbke; Johannes G. Filser; Ulrike Reuter; Heelmut Greim; Hermann Kappus; Klaus H. Norpoth; Peter Wardenbach; H.-Erich Wichmann (International Archives of Occupational and Environmental Health, 1998)

Turbulent Flux Measurements Above and Below the Overstory of a Boreal Aspen Forest - P.D. Blanken; T. A. Black; H. H. Neumann; G. Den Hartog; P. C. Yang; Z. Nesic; R. Staebler; W. Chen; M. D. Novak (Boundary-Layer Meteorology, 1998)

Biomonitoring of aromatic amines V: acetylation and deacetylation in the metabolic activation of aromatic amines as determined by haemoglobin binding - Iris Zwirner-Baier; Hans-Gü nter Neumann (Archives of Toxicology, 1998)

The exceptional Oder Flood in summer 1997 — the fate of nutrients and particulate organic matter in the Baltic Sea - C. Humborg; G. Nausch; T. Neumann; F. Pollehne; N. Wasmund (Ocean Dynamics, 1998)

The Validity of Similarity Theory in the Roughness Sublayer Above Forests - I. J. Simpson; G. W. Thurtell; H. H. Neumann; G. Den Hartog; G. C. Edwards (Boundary-Layer Meteorology, 1998)

Notification of Retraction: Interleukin 5 expressing allergen-specific T-lymphocytes in patients with house dust mite sensitization: analysis at a clonal level (1995) (J Mol Med 73(2):79-83 - R. Bonifer; C. Neumann; S. Meuer; G. Schulze; F. Herrmann (Journal of Molecular Medicine, 1997)

Observation of gravity waves in a boreal forest - X. Lee; H.H. Neumann; G. Hartog; R.E. Mickle; J.D. Fuentes; T.A. Black; P.C. Yang; P.D. Blanken (Boundary-Layer Meteorology, 1997)

Properties of tetrachloroethene and trichloroethene dehalogenase of Dehalospirillum multivorans - Anke Neumann; Gert Wohlfarth; G. Diekert (Archives of Microbiology, 1995)

Isolation and characterization of Dehalospirillum multivorans gen. nov., sp. nov., a tetrachloroethene-utilizing, strictly anaerobic bacterium - Heidrun Scholz-Muramatsu; Anke Neumann; Michael Memer; Edward Moore; G. Diekert (Archives of Microbiology, 1995)

Tetrachloroethene metabolism of Dehalospirillum multivorans - Anke Neumann; Heidrun Scholz-Muramatsu; G. Diekert (Archives of Microbiology, 1994)

Productive expression state confers resistance of human immunodeficiency virus (HIV)-2-infected lymphoma cells against superinfection by HIV-1 - G. K. von Dalnok; Andrea Kleinschmidt; M. Neumann; Christine Leib-Moesch; V. Erfle; Ruth Brack-Werner (Archives of Virology, 1993)

Quantification of haemoglobin binding of 4,4′-methylenebis(2-chloroaniline)(MOCA) in rats - G. Sabbioni; H. -G. Neumann (Archives of Toxicology, 1990)

Biomonitoring of aromatic amines III: Hemoglobin binding of benzidine and some benzidine congeners - G. Birner; W. Albrecht; H. -G. Neumann (Archives of Toxicology, 1990)

Contribution of olfactory navigation and non-olfactory pilotage to pigeon homing - Hans G. Wallraff; Michael F. Neumann (Behavioral Ecology and Sociobiology, 1989)

Biomonitoring of aromatic amines II: hemoglobin binding of some monocyclic aromatic amines - G. Birner; H. -G. Neumann (Archives of Toxicology, 1988)

Estimation of exposure of man to substances reacting covalently with macromolecules - P. B. Farmer; H. -G. Neumann; D. Henschler (Archives of Toxicology, 1987)

Biomonitoring of aniline and nitrobenzene - W. Albrecht; H. -G. Neumann (Archives of Toxicology, 1985)

Analysis of hemoglobin as a dose monitor for alkylating and arylating agents - H. -G. Neumann (Archives of Toxicology, 1984)

Methemoglobin formation and binding to blood constituents as indicators for the formation, availability and reactivity of activated metabolites derived from trans-4-aminostilbene and related aromatic amines - E. Wieland; H. -G. Neumann (Archives of Toxicology, 1978)

Metabolic activation of diethylstilbestrol and aminostilbene-derivatives - H. -G. Neumann; M. Metzler; W. Tpner (Archives of Toxicology, 1977)

Ultimate electrophilic carcinogens and cellular nucleophilic reactants - Hans -Gnter Neumann (Archives of Toxicology, 1974)